1977
DOI: 10.1111/j.1423-0410.1977.tb00602.x
|View full text |Cite
|
Sign up to set email alerts
|

Hæmostasis Disorders in Open Heart Surgery with Extracorporeal Circulation: Importance of the Platelet Function and the Heparin Neutralization

Abstract: The main haemostasis changes observed in a screening study performed in 40 patients who underwent an open heart surgery with extracorporeal circulation (ECC) are: a significant drop in platelet count from the onset of the ECC to the third postoperative day, a decrease of platelet retention and aggregation during ECC with an 8-day persistently increased heparin-neutralizing activity in plasma but not in serum, a moderate decrease of plasma factors I, II, VII-X, X and XIII and a more important drop in factor V w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1
2

Year Published

1983
1983
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(9 citation statements)
references
References 54 publications
(6 reference statements)
0
6
1
2
Order By: Relevance
“…Others have observed similar findings. 4 -519 ' 31 We found, as has been noted in a number of other clinical settings characterized by hemodilution, that platelet levels only rarely fell below 50 X io 9 /L. - 46 Without intervening complications such as massive tissue damage from shock or trauma, the bone marrow can maintain platelet counts at levels of approximately 50 X 10 9 /L in most patients.…”
Section: Changes In Hematologic Measurementsmentioning
confidence: 62%
See 1 more Smart Citation
“…Others have observed similar findings. 4 -519 ' 31 We found, as has been noted in a number of other clinical settings characterized by hemodilution, that platelet levels only rarely fell below 50 X io 9 /L. - 46 Without intervening complications such as massive tissue damage from shock or trauma, the bone marrow can maintain platelet counts at levels of approximately 50 X 10 9 /L in most patients.…”
Section: Changes In Hematologic Measurementsmentioning
confidence: 62%
“…4 ' 6,19,20,29~3 ' Our data reveal similar alterations in hemoglobin, platelet counts, fibrinogen, fibrin/fibrinogen degradation products, and factor V, VII, VIII, and IX levels (although our factor V nadirs were lower than some of those reported). 5,31 All levels declined within 15 minutes after patients were placed on CPB, remained low for the duration of CPB, and recovered at varying rates after discontinuation. Our study in patients undergoing hypothermic CPB demonstrated similar results to those reported in patients undergoing normothermic CPB.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of such procedures thrombocytopenia and loss of platelet haemostatic function occur and make an important contribution to the bleeding problems after charcoal haemoperfusion and Vane prolonged cardiopulmonary bypass in man. [18][19][20] Formation of microemboli during cardiopulmonary bypass may also contribute to cerebral complications which sometimes follow this procedure.21 Ainimal models of these extracorporeal circulations showed2 3 a platelet sparing effect of prostacyclin and this has now been confirmed in man.…”
mentioning
confidence: 99%
“…[527] δεν παρατήρησαν µείωση στην απώλεια αίµατος και στις απαιτήσεις για µετάγγιση, ούτε σηµαντική µείωση στη δόση της πρωταµίνης µε τη χρήση του συστήµατος RxDx. Από οκτώ δηµοσιευµένες µελέτες που συγκεκριµένα µελέτησαν την κλινική επίδραση της µειωµένης δόσης πρωταµίνης, τέσσερις ανέδειξαν είτε µειωµένη απώλεια αίµατος ή απαιτήσεις σε µετάγγιση [588,[522][523][524], και τέσσερις όχι [510,[525][526][527]. Η αντίφαση στο αποτέλεσµα µεταξύ των µελετών πιθανόν σχετίζεται µε διαφορές στη σχετική έκταση της µείωσης της δόσης της πρωταµίνης και στη συνολική αναλογία πρωταµίνης-ηπαρίνης στην οµάδα παρέµβασης.…”
Section: είναι λογική η χρήση είτε τιτλοποιηµένης πρωταµίνης είτε εµπunclassified
“…50% της ολικής δόσης ηπαρίνης) για µείωση της ολικής δόσης πρωταµίνης και για µείωση της αναλογίας πρωταµίνης-ηπαρίνης στο τέλος της CPB, προκειµένου να µειωθεί η αιµορραγία και οι απαιτήσεις σε µετάγγιση (Level of evidence B). Class IIbΤα πρωτόκολλα παρακολούθησης µπορούν σηµαντικά να επηρεάσουν τις δόσεις πρωταµίνης που χρειάζονται για να εξουδετερώσουν την ηπαρίνη [510,518,[522][523][524][525][526][527]. ∆ύο πρόσφατες µελέτες σύγκριναν τη χρήση ενός νέου διαγνωστικού αιµοστατικού συστήµατος (RxDx System, International Technidyne, Edison, New Jersey) µε το πρότυπο ACT βασισµένο σε εµπειρικό σχήµα στους ενήλικες ασθενείς που υπεβλήθησαν σε καρδιοχειρουργικές επεµβάσεις [518,527].…”
unclassified